An Electronic Atlas of Colloquial Arabic Language in the Arab World - Lee, Dong-Yul; Kang, Ji-Hoon; Moon, Sang-Ho; Youn, Yong-Su (International Journal of Engineering and Technology, 2019)
The Arab world needs to be researched in its entirety and not in single units such as countries. We suggest a new research unit based on colloquial Arabic language which has an important position in Arab identity. In detail, we set up research units for the Arab region based on differences in pronunciations of colloquial Arabic language. In order to do this, we collected colloquial Arabic language textbooks and broadcasting materials in various Arab countries. Based on these materials we created a database of colloquial Arabic language pronunciations for each Arab country and developed an electronic atlas based on that database. Subsequently, the electronic map was analyzed for defining new research units for area studies of the Arab region.